Etonogestrel and Alzheimer's: A multi-scale computational approach to acetylcholinesterase inhibition - Kunal Bhattacharya; Nongmaithem Randhoni Chanu; Pukar Khanal; Atanu Bhattacharjee; Manodeep Chakraborty; Dibyajyoti Das (Next Materials)
Background: This study explores Etonogestrel, a synthetic progestin used in hormonal contraceptives, as a potential Acetylcholinesterase (AChE) inhibitor for treating Alzheimer's disease. Methods: The study involved analyzing Etonogestrel's molecular properties, preparing AChE macromolecules, and conducting molecular docking and dynamics simulations. Techniques like MM-GBSA, dynamic cross-correlation matrix, and principal component analysis were used to assess Etonogestrel's interaction with AChE. Results: Etonogestrel demonstrated a strong binding affinity to AChE, primarily through van der Waals and pi-interactions. Molecular dynamics simulations indicated a stable binding mode, suggesting Etonogestrel's potential as a reversible AChE inhibitor. Conclusion: The findings suggest that Etonogestrel might have promising cognitive-enhancing properties through its interaction with AChE. However, the study emphasizes the need for experimental validation to confirm its therapeutic efficacy and safety.